ANALISA HARGA EMAS TERHADAP PENDAPATAN SEWA MODAL PERIODE 2008 – 2010 PADA PERUM PEGADAIAN CABANG BLOK A JAKARTA - Manullang, Asna (STIE Binaniaga, 2012)
Gold price analysis of revenue capital lease period 2008 – 2010 in a block branch pawnshop Jakarta. The gold price used in the pawnshop branches Blok. A always be corrected in accordance with development of the gold price in the market so that the rice and fall of the price of gold will have a positive impact on the rental income of capital . Rise and fall of the price of gold will continue to be a concern especially with the mortgage capital rental rates will affect the rental income of capital, The result of the correlation analysis with SPSS above it is evident that the relationship / correlation between the price of gold with a capital of 0.377 rental income, but the relationship between the two variables is low. While the directions do show positive (positive r) which means that the higher the price of gold, the higher the capital rental income to be earned.Keyword. gold price. capital lease revenue